2013
DOI: 10.1073/pnas.1312374110
|View full text |Cite
|
Sign up to set email alerts
|

Pooled RNAi screen identifies ubiquitin ligase Itch as crucial for influenza A virus release from the endosome during virus entry

Abstract: Influenza viruses, like other viruses, rely on host factors to support their life cycle as viral proteins usually "hijack," or collaborate with, cellular proteins to execute their functions. Identification and understanding of these factors can increase the knowledge of molecular mechanisms manipulated by the viruses and facilitate development of antiviral drugs. To this end, we developed a unique genome-wide pooled shRNA screen to search for cellular factors important for influenza A virus (IAV) replication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 34 publications
0
101
0
Order By: Relevance
“…We previously carried out an RNA interference (RNAi) screen and identified RRP1B as one of the candidates potentially affecting IAV replication (12). To verify its role in IAV replication, A549 cells were first transduced with lentiviruses expressing the shRNAs targeting RRP1B and then infected with influenza A/WSN/33 virus for 6 h. Compared to the shLacZ control, shRRP1B no.…”
Section: Identification Of Rrp1b As An Important Cofactor For Influenzamentioning
confidence: 99%
See 1 more Smart Citation
“…We previously carried out an RNA interference (RNAi) screen and identified RRP1B as one of the candidates potentially affecting IAV replication (12). To verify its role in IAV replication, A549 cells were first transduced with lentiviruses expressing the shRNAs targeting RRP1B and then infected with influenza A/WSN/33 virus for 6 h. Compared to the shLacZ control, shRRP1B no.…”
Section: Identification Of Rrp1b As An Important Cofactor For Influenzamentioning
confidence: 99%
“…Unfortunately, relatively few overlaps among the candidates were found. We therefore carried out a modified pooled genome-wide RNAi library screen (12). In total, 38 candidate genes, hit by two unique short hairpin RNAs (shRNAs) showing at least 40% reduction of viral replication, were identified as hits.…”
mentioning
confidence: 99%
“…EGFR is a receptor tyrosine kinase (RTK) that acts upstream of MAPK1 and has been implicated in IAV infection. During a recently published RNA interference screen for host factors of IAV, EGFR was one of the best-performing candidates (29). In addition, Eierhoff and colleagues have demonstrated that EGFR is activated following IAV attachment, which in turn promotes the uptake of virions into cells (39), thereby providing evidence for a role of EGFR during IAV entry.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide small interfering RNA (siRNA) screens are a powerful tool to identify host factors associated with viral infections. Several such screens have been performed to determine cellular factors required by IAV during infection (23)(24)(25)(26)(27)(28)(29)(30). Surprisingly, there was hardly any overlap between the primary hits identified in these screens (31).…”
mentioning
confidence: 99%
“…Phosphorylation of M1 at Y132 mediates the nuclear import of M1 (23), whereas SUMOylation of M1 regulates the nuclear export of vRNPs and promotes virion assembly and budding (21). Ubiquitination of M1 has been implicated in IAV release from the endosomes (24). However, the precise modification site and the biological functions of M1 ubiquitination are not well understood.…”
mentioning
confidence: 99%